Location privacy preserving scheme based on dynamic pseudonym swap zone for Internet of Vehicles - Min Yang; Yong Feng; Xiaodong Fu; Qian Qian (International Journal of Distributed Sensor Networks)
In Internet of Vehicles, establishing swap zones in which vehicles can exchange pseudonyms is an effective method to enhance vehicles’ location privacy. In this article, we propose a new scheme based on dynamic pseudonym swap zone, to protect location privacy of vehicles. For each vehicle, dynamic pseudonym swap zone allows it dynamically to establish a temporary pseudonym swap zone on demand to exchange the pseudonym with another random vehicle in the just formed zone. This randomness of choosing the pseudonym exchanging vehicles prevents dynamic pseudonym swap zone from the secure risk that the information of exchanging participants exposes to their group manager in some existing works in which each pair of pseudonym exchanging participants is assigned by the manager. To avoid the high communication and computation overhead of frequently swapping pseudonyms, dynamic pseudonym swap zone adopts a combination of swap and update to achieve the unlinkability between new and previous pseudonyms. Moreover, dynamic pseudonym swap zone can self-adapt to the varying surroundings to reduce the communication cost of forming pseudonym swap zones in high vehicle density areas. The analysis and simulation results show that our proposed dynamic pseudonym swap zone is a high location privacy preserving, secure, auditable scheme.